Genetic regulation of newborn telomere length is mediated and modified by DNA methylation - Wang, Congrong; Alfano, Rossella; Reimann, Brigitte; Hogervorst, Janneke; Bustamante, Mariona; De Vivo, Immaculata; Plusquin, Michelle; Nawrot, Tim S.; Martens, Dries S. (Frontiers in Genetics, 2022)
Telomere length at birth determines later life telomere length and potentially predicts ageing-related diseases. However, the genetic and epigenetic settings of telomere length in newborns have not been analyzed. In addition, no study yet has reported how the interplay between genetic variants and genome-wide cytosine methylation explains the variation in early-life telomere length. In this study based on 281 mother-newborn pairs from the ENVIRONAGE birth cohort, telomere length and whole-genome DNA methylation was assessed in cord blood and 26 candidate single nucleotide polymorphism (SNP) related to ageing or telomere length were genotyped. We identified three genetic variants associated with cord blood telomere length and 57 cis methylation quantitative trait loci (cis-mQTLs) of which 22 mQTLs confirmed previous findings and 35 were newly identified. Five SNPs were found to have significant indirect effects on cord blood telomere length via the mediating CpGs. The association between rs911874 (SOD2) and newborn telomere length was modified by nearby DNA methylation indicated by a significant statistical interaction. Our results suggest that DNA methylation in cis might have a mediation or modification effect on the genetic difference in newborn telomere length. This novel approach warrants future follow-up studies that are needed to further confirm and extend these findings.